Patients with essential tremor can have manual dexterity and attention deficits with no impairments in other cognitive functions - Medeiros, Leonardo Mariano Inácio; Castro, Pollyanna Celso Felipe de; Felício, André C.; Queiros, Bárbara Bernardo; Silva, Sonia Maria Cesar Azevedo; Ferraz, Henrique Ballalai; Bertolucci, Paulo Henrique Ferreira; Borges, Vanderci (Arquivos de Neuro-Psiquiatria, 2016)
Essential tremor (ET) was long believed to be a monosymptomatic disorder. However, studies have evidenced structural changes and attention is now being focused on non-motor symptoms. The objective of the study is to describe and compare ET patients with control groups according to their cognitive functions, and secondarily, to compare their sociodemographic characteristics and other clinical features. All participants were assessed using the Fahn-Tolosa-Marin Tremor Rating Scale for the severity of tremor; a neuropsychological assessment battery and a screening questionnaire for mood and anxiety symptoms. There were no significant age and gender differences between all groups. As for neuropsychological assessment results, a significant difference was found only in the Pegboard test. We also found a significant negative correlation between a poorer cognitive test results and disease severity and a significant differences regarding depression or anxiety symptoms in patients with ET. The study results suggest that patients with ET have impaired manual dexterity and attention.
Keywords: essential tremor; cognition; anxiety; depression; manual dexterity